Monkeypox in the COVID-19 era - Lazar, Angela Madalina (Journal of Ideas in Health, 2022)
Currently, in addition to the COVID-19 waves, the world is confronting an additional threat: the global monkeypox infection outbreak, already regarded as a “public health emergency of international concern” by the World Health Organization. According to the most recently published reports, more than 21000 monkeypox infection cases have been confirmed in 78 countries, with 5 African deaths and more than three deaths outside endemic Africa while the numbers are still increasing. Too little is currently known about the monkeypox virus, although it does not appear as a recently emerged pathogen, being probably as ancient as the smallpox virus. The major fear in regards to the current international monkeypox infection spread has multiple causes: monkeypox's similarity to smallpox, the deadliest pathogen in the history of humanity; lack of knowledge of the virus's natural occurrence, animal reservoir, mechanisms of transmission, pathogenicity, host immune response; lack of effective specific treatment and vaccine; unusually rapid geographic spread and atypical clinical presentation; increase in the mutation rate outside the standard, mathematically anticipated rates; putative complications and sequelae of the infection; potential use as a biological weapon. Actually, with such characteristics, the monkeypox virus has the potential to occupy/replicate the place of the much-feared smallpox virus. In the near future, due to the high registry of viral mutagenesis, limitations in the preventive strategies, and lack of an efficient vaccine, several viruses, including SARS-CoV-2 and monkeypox, could continue their worldwide spread and generate flu-like subsequent infective bursts. Therefore, dedicated research and detailed knowledge of the viral pathogenic mechanisms and transmission routes are required to design efficient therapies and limit/stop future pandemics: until the emergence of a new virus.